EXTENT OF SLEEP QUALITY AMONG STUDENTS OF INDIA AND IRAN: A COMPARATIVE STUDY - Prikamali, Somayyeh; D’Souza, Lancy (International Journal of Psychosocial Rehabilitation, 2020)
In the recent years there have been many studies and researches which have been focused on sleep quality from different parts around the world. Sleep quality of an individual plays very important role in his/her bio-psycho-social functioning. Present study attempted compare and find out extent of sleep quality among students in India and Iran. The sample consisted of 388 students of which 195 were Indian and 193 were Iranian students who were randomly selected from few colleges in India and Iran. The randomly selected students were subjected to the Pittsburgh Sleep Quality Index (PSQI-1989) scale which measured global sleep quality with 7 components. Two way ANOVA was employed to find out the difference among students in terms of country and gender along with interaction effects. Results revealed that Indian students experienced poorer sleep quality than Iranian students, more so in the case of subjective sleep quality and sleep disturbance. Gender comparison revealed that sleep latency scores and sleep efficiency was poorer for female students and sleep disturbance was poorer for male students. Female students of India had poor subjective sleep quality, Iranian female students had poorer sleep efficiency and more use of sleep medication